The Speaking Stutter: Analyzing What Makes Seventh Graders Fear English Conversation - Asrid Noni Lende; Ike Dian Puspita Sari (UIBU, 2024)
This research is a descriptive qualitative research. The subjects of this study were students of 7th Grader. There are 25 students, in conducting observations 25 students are taken and interviews in each class there are 5 students taken in each class, so the number of students interviewed is 15 students. Data collection is done by observation and interview. The data was analyzed using Horwitz's theory: Causes of student speaking anxiety. The researcher analyzed the data through students' interview answers. The results of the research findings are that seventh grade students of have several anxiety factors, namely fear of speaking in front of the class, lack of vocabulary, fear of being laughed at by friends, lack of preparation, low English language skills, lack of practice in English, and lack of confidence when students come forward to the class .